AUTONOMOUS SYSTEMS IN INDUSTRY 5.0: ENHANCING HUMAN ROBOT COLLABORATION AND SAFETY IN INDONESIAN MANUFACTURING - Lucas Lima; Tiago Costa; Li Wei; Rustiyana Rustiyana (Yayasan Adra Karima Hubbi, 2025)
Industry 5.0 represents a fundamental shift toward a more human-centric paradigm in manufacturing by emphasizing enhanced collaboration between humans and robots, where autonomous systems are designed not only to optimize efficiency but also to improve safety and support workers in performing more complex and value-added tasks. In the Indonesian manufacturing context, the adoption of autonomous technologies is accelerating as industries seek to remain competitive; however, empirical evidence regarding their effectiveness in improving human-robot collaboration and workplace safety remains limited. This study addresses this gap by exploring the role of autonomous systems in Industry 5.0 and examining how integrated safety protocols and collaboration strategies can enhance both operational efficiency and occupational safety. Employing a mixed-methods approach, the research combines qualitative insights from interviews with industry experts and quantitative data derived from experimental implementations of autonomous robotic systems in Indonesian manufacturing environments. The findings demonstrate that the deployment of adaptive safety systems significantly strengthens human-robot collaboration, resulting in a 30% reduction in workplace accidents and a 20% increase in production efficiency. These results indicate that well-designed autonomous systems can effectively minimize risks while enabling workers to interact more confidently and productively with robots, thereby supporting the conclusion that Industry 5.0 technologies hold substantial potential for improving safety standards and overall performance in Indonesian manufacturing settings.